Integration of LoRa IoT with cloud platform in stingless beehive remote monitoring system - Ahmad, Yasser Arul; Nurul Salshabila, Mustapa; Anis Hannani, Razaman; Muhammad Nasrin Aqil, Abdul Hamid; Noreha, Abdul Malik; Mohd Faizal, Jamlos (International Islamic University Malaysia-IIUM, 2025)
Stingless bee colonies require constant monitoring to ensure hive health and optimal honey production. However, conventional monitoring practices are time-consuming and labor-intensive, especially for beekeepers in rural or remote areas. Without access to real-time hive data, beekeepers may struggle to detect changes in temperature, humidity, and other vital conditions that could impact bee health and productivity. Most studies rely on Wi-Fi modules for communication between local and cloud servers. However, using Wi-Fi for bee monitoring requires that the stingless bee hives be located near buildings with Wi-Fi access. To address this issue, a prototype of a remote monitoring system for a stingless bee colony was developed using Long Range (LoRa) technologies due to the low data rate, low power, and operability in an outdoor environment. This system aims to help beekeepers monitor the beehives remotely. The prototype comprises two nodes: a beehive sensor node and a LoRa gateway node. The beehive monitoring sensor node is equipped with the ESP32 as a microcontroller, LoRa SX1278, BME680, and KY-037. The LoRa gateway comprises ESP32 and LoRa SX1278 and is interfaced with Ubidots through Node-Red. The developed prototype was tested at four locations at varying distances in the Mahallah Ruqayyah Kelulut farm. The result shows that LoRa is feasible for remote monitoring because it can reliably transmit data up to 58 meters despite a higher data rate. The Ubidots dashboard displays the temperature, humidity percentage, air quality, pressure, sound levels, and RSSI value for thorough insights into the bee's condition, as it can be accessed using web and mobile applications. Overall, the stingless bee remote monitoring system using LoRa communication is a promising solution for outdoor applications between the sender and receiver for data transmission in remote areas.